Between-population outbreeding affects plant defence - Leimu, R; Fischer, M (Public Library of Science, 2010)
Between-population crosses may replenish genetic variation of populations, but may also result in outbreeding depression. Apart from direct effects on plant fitness, these outbreeding effects can also alter plant-herbivore interactions by influencing plant tolerance and resistance to herbivory. We investigated effects of experimental within- and between-population outbreeding on herbivore resistance, tolerance and plant fitness using plants from 13 to 19 Lynchis flos-cuculi populations. We found no evidence for outbreeding depression in resistance reflected by the amount of leaf area consumed. However, herbivore performance was greater when fed on plants from between-population compared to within-population crosses. This can reflect outbreeding depression in resistance and/or outbreeding effects on plant quality for the herbivores. The effects of type of cross on the relationship between herbivore damage and plant fitness varied among populations. This demonstrates how between-population outbreeding effects on tolerance range from outbreeding depression to outbreeding benefits among plant populations. Finally, herbivore damage strengthened the observed outbreeding effects on plant fitness in several populations. These results raise novel considerations on the impact of outbreeding on the joint evolution of resistance and tolerance, and on the evolution of multiple defence strategies.